5p-11=9p+7

Simple and best practice solution for 5p-11=9p+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-11=9p+7 equation:


Simplifying
5p + -11 = 9p + 7

Reorder the terms:
-11 + 5p = 9p + 7

Reorder the terms:
-11 + 5p = 7 + 9p

Solving
-11 + 5p = 7 + 9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9p' to each side of the equation.
-11 + 5p + -9p = 7 + 9p + -9p

Combine like terms: 5p + -9p = -4p
-11 + -4p = 7 + 9p + -9p

Combine like terms: 9p + -9p = 0
-11 + -4p = 7 + 0
-11 + -4p = 7

Add '11' to each side of the equation.
-11 + 11 + -4p = 7 + 11

Combine like terms: -11 + 11 = 0
0 + -4p = 7 + 11
-4p = 7 + 11

Combine like terms: 7 + 11 = 18
-4p = 18

Divide each side by '-4'.
p = -4.5

Simplifying
p = -4.5

See similar equations:

| 300=-222+a | | 6u-u= | | 0.80x+0.40(150)=0.40(150) | | 36+y=-66 | | 35=21y-7 | | 2x^2-9x+12=0 | | -14=-9z-16 | | 0=-5w+15 | | (x-6)=2x-12 | | 3+5x-6+2x=-4(x-3)+7 | | 36=-44+a | | .5(6x-8)=1.4(x-5)-.2 | | 36=-44+2 | | 0=6u-31 | | 0=6u-31 | | 11=-12+c | | 5h-12=4h+7 | | -8x+29=-7x | | 3=11+a | | .7(3x-5)+3.9x=14.5 | | 1-10x=91 | | 6x-12=8x-9 | | 2x-1=+11 | | -46-14n=-8(-6b+1) | | 3d+3c+5c= | | (7a+3)+(-a-5)=14 | | 9x^2-6x+6=0 | | -7(x+1)+(14x)=7(x+3)-14 | | 2/3(x+5)=4/9 | | 2m^2+10m=-12 | | 130-7x=38x+20 | | 32w^3-2v^4w^3=0 |

Equations solver categories